2022
DOI: 10.1111/gcb.16549
|View full text |Cite
|
Sign up to set email alerts
|

Abundance trends for river macroinvertebrates vary across taxa, trophic group and river typology

Abstract: Biodiversity is rapidly changing across the globe (Díaz et al., 2019).Long-term datasets suggest widespread declines in richness, abundance and biomass of terrestrial insects and other arthropods, including steep declines in biomass of flying insects in areas of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…This aspect needs further work, especially where better abundance or biomass data are available (e.g. Powell et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect needs further work, especially where better abundance or biomass data are available (e.g. Powell et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…March-May was the most frequently used sample period, so this choice maximised the sample size in space and time, whilst minimising the risk of artefacts caused by variation in sample timing across the study period. A joint quality-assurance scheme for England andWales (1991-2011) indicated that the error rate was nearconstant (Murray-Bligh and Griffiths, 2022), and similar protocols remained in place subsequently for sample processing in the two countries. Sampling sites were included if they: i) had been sampled in at least four years during 1991-2019, including at least one sample in each decade (1991-2000, 2001-2010 and 2011-2019); ii) were not directly downstream from an effluent outfall; iii) included data on altitude, distance from source and channel slope; and iv) could have their catchments delineated from a digital terrain model.…”
Section: Macroinvertebrate Datamentioning
confidence: 99%
“…Indeed, Myers & Worm [157] explicitly note that compensatory responses of smaller fish species have been observed even though they were not part of their analysis. Per cent cover (a metric of biomass) of living coral on reefs has also shown large declines globally [71], while diatom abundances show spatially variable trends related to climate, without a strong overall general trend [158,159].…”
Section: (D) Abundance and Biomassmentioning
confidence: 99%
“…This method could be applied to other chemical species or geographical regions. Future studies could also investigate the method's applicability to river biodiversity indicators such as macroinvertebrate abundance (Powell et al, 2022).…”
Section: Challenges Limitations and Future Workmentioning
confidence: 99%